1994
DOI: 10.1111/j.1348-0421.1994.tb02141.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Thymocyte and Thymic Low‐Density Adherent Cell Functions

Abstract: Thymocytes which have developed in the C3H thymus showed depressed proliferative responses to stimulation with anti‐CD3 antibody as compared with those which have developed in the thymus of other strains of mice (i.e. AKR). The present study was conducted to analyze immunological functions of the thymic stromal cell population (low‐density adherent cells, LDAC) in the C3H mice using allogeneic bone marrow (BM) chimeras established by BM transplantation in the reciprocal combination of AKR and C3H mice as donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…[HE staining (A, B, G, and H) ϭ ϫ40; immunohistochemical staining (C, D, E, and F) ϭ ϫ400. ] of the thymus (15,16,(25)(26)(27)(28)(29), although it has been shown that macrophages and dendritic cells derived from BM precursors were partially involved in functional maturation of thymocytes (30). The present findings demonstrated once again that the developmental arrest of NK1.1 ϩ TCR-␣͞␤ ϩ thymocytes in aly͞aly mouse is associated with structural abnormalities of the thymus that are peculiar to the aly͞aly mouse.…”
Section: Nk11supporting
confidence: 57%
“…[HE staining (A, B, G, and H) ϭ ϫ40; immunohistochemical staining (C, D, E, and F) ϭ ϫ400. ] of the thymus (15,16,(25)(26)(27)(28)(29), although it has been shown that macrophages and dendritic cells derived from BM precursors were partially involved in functional maturation of thymocytes (30). The present findings demonstrated once again that the developmental arrest of NK1.1 ϩ TCR-␣͞␤ ϩ thymocytes in aly͞aly mouse is associated with structural abnormalities of the thymus that are peculiar to the aly͞aly mouse.…”
Section: Nk11supporting
confidence: 57%
“…The secreted PGE2 was quantitated using a competitive enzyme immunoassay kit (Cayman). The assays were carried out according to the protocol supplied with the kit as described [24].…”
Section: Pgel Production Assaymentioning
confidence: 99%